Calibrated ages of Escondido (PAT-ESC-2010) peat core from Patagonia - Julie Loisel (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.